Understanding Cognitive Engagement in Online Discussion: Use of a Scaffolded, Audio-based Argumentation Activity - Oh, Eunjung; Kim, Hyun (International Review of Research in Open and Distributed Learning, 2016)
The purpose of this paper is to explore how adult learners engage in asynchronous online discussion through the implementation of an audio-based argumentation activity. The study designed scaffolded audio-based argumentation activities to promote students’ cognitive engagement. The research was conducted in an online graduate course at a liberal arts university. Primary data sources were learners’ text-based discussions, audio-recorded argumentation postings, and semi-structured interviews. Findings indicate that the scaffolded, audio-based argumentation activity helped students achieve higher levels of thinking skills as well as exert greater cognitive efforts during discussions. In addition, most students expressed a positive perception of and satisfaction with their experience. Implications for practice and future research areas are discussed.